Dlouhodobé výsledky CLS jamky u primární náhrady kycle - Rozkydal, Z; Janícek, P; Tomás, T; Florian, Z (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2009)
PURPOSE OF THE STUDY To evaluate the results of primary total hip replacement with the CLS acetabular cup at a minimum of 15 years of follow- up. MATERIAL AND METHODS A total of 105 patients, with 112 hips, undergoing hip arthroplasty with the use of CLS acetabular cup between 1991 and 1993 were evaluated. The group comprised of 33 men and 72 women with an average age of 51.3 years (range, 28 to 66) at the time of surgery. All patients received the CLS expansion cup with a polyethylene Sulen-type liner. Cemented femoral stems were used in 75 hips and uncemented CLS stems were implanted in 37 hips. Ceramic heads of the femoral component were used in 86 hips and metal heads were used in 26 hips. The clinical outcome was assessed by the Merle dAubignnd Postel score and the Harris hip score, and the radiological results were evaluated on anterior posterior X-ray films of the pelvis and the affected hip. RESULTS The average follow-up was 16.2 years (range, 15 to 17). The average Merle dAubignnd Postel score increased from 8.1 (range, 5.7 to 9.8) pre-operatively to 14.6 (range, 14.1 to 16.8) post-operatively. The average Harris hip score improved from 42 to 86 points (range, 71 to 99). The complications requiring revision arthroplasty included aseptic loosening in two hips, fracture of the CLS shell in three, dislocation in three and replacement of the liner due to high wear in two hips. The cumulative proportion of clinical survivorship with revision for any reason was 92 %. Fixation by bone ingrowth, assessed by the method of Engh et al. occurred in 98 cases, fibrous tissue fixation was found in ten hips. Unstable fixation was recorded in four hips (two with aseptic loosening and two with fracture of the shell). There were no signs of rarefaction of bone along acetabular shell in 98 hips. No noticeable migration was found in the stable cups. Only in ten cups from 112, polyethylene wear exceeded 4 mm. Cumulative probability of radiological survivorship of the CLS acetabular cup with any radiological sign of loosening was 86.6 %. DISCUSSION The causes of fracture of the CLS cup can be explained by insufficient bone support or bone resorption in the proximallateral part of the acetabulum in patients with developmental hip dysplasia, by low bone quality due to severe osteoporosis or by insufficient primary stability of the cup. The advantages of the CLS cup include removal of a small amout of bone and favourable force distribution in circumferential anchorage. The cup showed good osteointegration even in a bone of lower quality and with defects of the acetabular bottom. CONCLUSIONS The CLS acetabular cup shows good results at 16-year follow-up period. No increase in fractures of the shell, migration or radiolucent lines, or in bone rarefaction or osteolysis was recorded with time. The reliability of this implant has been recently increased with the use of cross-linked polyethylene (Durasul). Key words: primary total hip replacement, uncemented cup.
Keywords: dospělí; Female; kyčelní kloub; radiografie; kyčelní protézy; Radiography; Adult; ženské pohlaví; Acetabulum; lidé; následné studie; acetabulum; Reoperation; reoperace; Hip Joint; Follow-Up Studies; selhání protézy; Male; Aged; náhrada kyčelního kloubu; lidé středního věku; Arthroplasty, Replacement, Hip; senioři; mužské pohlaví; Middle Aged; Hip Prosthesis; Prosthesis Failure; Humans